Glycogen Synthase Kinase-3 Beta Expression Correlates With Worse Overall Survival in Non-Small Cell Lung Cancer—A Clinicopathological Series - Alves, Marclesson; Borges, Daniela de Paula; Kimberly, Aline; Martins Neto, Francisco; Oliveira, Ana Claudia; Sousa, Juliana Cordeiro de; Nogueira, Cleto D.; Carneiro, Benedito A.; Tavora, Fabio (Frontiers in Oncology, 2021)
BACKGROUND: Glycogen Synthase Kinase-3 beta (GSK-3) regulates diverse cellular functions including metabolic activity, signaling and structural proteins. GSK-3 phosphorylates target pro-oncogenes and regulates programmed cell death-ligand 1 (PD-L1). This study investigated the correlation between GSK-3 expression and clinically relevant molecular features of lung adenocarcinoma (PDL1 score, PTEN expression and driver mutations). METHODS: We evaluated 95 specimens of lung cancer from biopsies and surgical resections. Immunohistochemistry was performed to analyze the expression of GSK-3, PTEN and PDL1. Epidemiological data, molecular characteristics and staging were evaluated from medical records. The histologic classification was performed by an experienced pulmonary pathologist. RESULTS: Most patients were female (52.6%) and the majority had a positive smoking history. The median age was 68.3 years, with individuals over 60 years accounting for 82.1%. The predominant histological subtype was adenocarcinoma (69.5%) followed by squamous cell carcinoma type (20.0%). GSK-3 expression in tumors was cytoplasmic with a dotted pattern and perinuclear concentration with associated membranous staining. Seven (7.3%) tumors had associated nuclear localization of expression. Seventy-seven patients (81.1%) had advanced clinical-stage tumors. GSK-3 was positive in 75 tumors (78%). GSK3-positive tumors tended to be diagnosed in advanced stages. Within stage III/IV tumors, 84% had GSK3 positivity (p= 0.007). We identified a statistically significant association among GSK-3 and PTEN in the qualitative analysis (p 0.021); and when compared PTEN to GSK-3 intensity 2+ (p 0.001) or 3+ expression (> 50%) – p 0.013. GSK-3 positive tumors with a high histologic score had a worse overall survival. CONCLUSION: We identified the histologic patterns of GSK-3 expression and evaluated its potential as marker for overall survival, establishing a simple histologic score to measure to evaluated status in resected tissues. The use of GSK-3 expression as an immune response biomarker remains a challenge. Future studies will seek to explain the role of interaction with PTEN.